Efek Antihipertensi Ekstrak Etanol Daun Sembung (Blumea balsamifera) pada Model Hewan Uji Induksi Epinefrin - Sutjiatmo, Afifah Bambang; Bintussolihah, Falna; Vikasari, Suci Nar (Jurnal Farmasi Indonesia, 2019)
Hypertension is a non-communicable disease that has a high prevalence. Blumea balsamifera(Asteraceae) is one of the plants that has traditionally been used to treat high blood pressure. The aim of this study is to evaluate antihypertensive effect of ethanol extract of Blumea balsamiferaleaves on animal models induced epinephrine. The extract was made in 50% ethanol. Extraction was done using a set of Soxhlet tools. The antihypertensive effect test was carried out on male Wistar rats using epinephrine 0.25 mg/kg bwas inductor and blood pressure was measured indirectly through the tail using Kent Scientific's CODA system. The dose of extract was 8.75; 17.5 and 35 mg/kg bw, while propranolol at dose dose 1.8 mg/kg bw was used as comparator. The parameters were diastolic and systolic blood pressure. The results showed that the ethanol extract at doses of 8.75; 17.5 and 35mg/kg bw can prevent the increase in diastolic and systolic blood pressure in animals model induced epinephrine when compared to controls (p <0.05), where the best results is shown by the ethanol extract at dose of 17.5 mg/kg bw. The ability of the ethanol extract is equivalent to propranolol (p> 0.05). It can be concluded that Blumea balsamiferaleaves can be developed and have the potential to be antihypertensive.